Role of Dicer1 in thyroid cell proliferation and differentiation. Issue 23 (2nd December 2017) - Penha, Ricardo Cortez Cardoso; Sepe, Romina; De Martino, Marco; Esposito, Francesco; Pellecchia, Simona; Raia, Maddalena; del Vecchio, Luigi; Decaussin-Petrucci, Myriam; De Vita, Gabriella; Pinto, Luis Felipe Ribeiro; Fusco, Alfredo
ABSTRACT: DICER1 plays a central role in the biogenesis of microRNAs and it is important for normal development. Altered microRNA expression and DICER1 dysregulation have been described in several types of tumors, including thyroid carcinomas. Recently, our group identified a new somatic mutation (c.5438A>G; E1813G) within DICER1 gene of an unknown function. Herein, we show that DICER1 is overexpressed, at mRNA level, in a significant-relative number of papillary (70%) and anaplastic (42%) thyroid carcinoma samples, whereas is drastically downregulated in all the analyzed human thyroid carcinoma cell lines (TPC-1, BCPAP, FRO and 8505c) in comparison with normal thyroid tissue samples. Conversely, DICER1 is downregulated, at protein level, in PTC in comparison with normal thyroid tissues. Our data also reveals that DICER1 overexpression positively regulates thyroid cell proliferation, whereas its silencing impairs thyroid cell differentiation. The expression of DICER1 gene mutation (c.5438A>G; E1813G) negatively affects the microRNA machinery and cell proliferation as well as upregulates DICER1 protein levels of thyroid cells but has no impact on thyroid differentiation. In conclusion, DICER1 protein is downregulated in papillary thyroid carcinomas and affects thyroid proliferation and differentiation, while DICER1 gene mutation (c.5438A>G; E1813G) compromises the DICER1 wild-type-mediated microRNA processing and cell proliferation.